USE OF APPLIED LINGUISTICS PROGRAMS IN TEACHING LEGAL DISCIPLINES IN ENGLISH - Liudmyla Balykina-Halanets (Неперервна професійна освіта: теорія та практика)
In this article, we address several key questions related to teaching a professional discipline in English. Specifically, we explore how to select appropriate materials, assess text complexity, and compile a list of terms for vocabulary study. We argue that an effective course requires the instructor to possess both subject matter expertise and effective foreign language teaching methods. Our focus is on the process of preparing and teaching English-language material within a professional discipline at the university level. We emphasize the use of search engines such as VOICE (Vienna-Oxford International Corpus of English), ELFA CORPUS (English as a Lingua Franca Academic Corpus), and MICASE (Michigan Corpus of Undergraduate Student Papers) to locate academic material. Additionally, we discuss methods for assessing text complexity, including using language proficiency levels from A1 to C2 to gauge a student's comprehension. We also propose an experimental approach to determining the necessary vocabulary for understanding a given text. To aid in forming vocabulary and evaluating text complexity, we recommend utilizing interactive tools from the field of applied linguistics, such as Ant Conc, a program that offers free corpus analysis tools, and Multiling Profiler, an online tool for analyzing word frequency.